On the Stipulation of Autonomy of Will Principle by the Bustamante Code - T. V. Novikova (Московский журнал международного права, 2019)
INTRODUCTION. Autonomy of will principle (mainly, in case of international contracts) is firmly established in modern private international law. It has become more and more widespread in international treaties unifying choice of law and national legislation of numerous states through the whole XX century. The jurisprudence elaborated a position that the first comprehensive codification of private international law (the Bustamante Code) stipulates autonomy of will principle for parties to international private relations.MATERIALS AND METHODS. The essential technique of this research is bases on the analysis dealing not only with the text of the Bustamante Code, but more with the framework and effects of its elaboration as well as with the peculiarities of its application by member states (especially in the view of general reservations made by several states).RESEARCH RESULTS. It is pointed out that the Bustamante Code as comprehensive codification of private international law is based on compromise solutions and has been ratified with multiple reservations including those nullifying the very idea of unification. It is proved in series that art. 3 of the Bustamante Code, outlining three categories of legal norms (including voluntary, “applied only by manifestation, interpretation or presumption of will of the parties or one of the parties”), has too broad character, and fragmentary autonomy of will mentioning in respect of contracts’ interpretation and choice-oflaw rules dealing with contracts of adhesion are not sufficient to contend that the Bustamante Code has proclaimed, stipulated or even acknowledged the autonomy of will principle in private international law.DISCUSSION AND CONCLUSIONS. Two main conclusions are made: firstly, contrary to the point of view widespread in jurisprudence the grounds to contend that the Bustamante Code proclaims autonomy of will principle are absent; secondly, conclusion on legal principle stipulation by the international treaty (or by the other form of law) requires, in author’s opinion, quite definite terminology of provision or of the whole text of the corresponding document in the view of concept description and specific peculiarities of its mechanism.